A case of diaphragmatic hernia incarceration after a heart transplant operation. Issue 1 (25th May 2020) - Sasaki, Masaru; Takahashi, Tsuyoshi; Funaki, Soichiro; Tanaka, Koji; Miyazaki, Yasuhiro; Ose, Naoko; Makino, Tomoki; Kurokawa, Yukinori; Yamasaki, Makoto; Nakajima, Kiyokazu; Shintani, Yasushi; Mori, Masaki; et al.
Abstract: We report a case of a diaphragmatic hernia after a heart transplant operation. A 43‐year‐old woman, who underwent orthotropic heart transplantation for hypertrophic cadiomyopathy two year earlier, presented with vomiting and epigastric pain. A computed tomography scan showed that the stomach and transverse colon were dislocated in the left thoracic cavity. We diagnosed left diaphragmatic hernia incarceration and performed laparoscopic repair of the diaphragmatic hernia. A 12 × 8 cm diaphragmatic defect was found intraoperatively on the ventrolateral aspect of the left diaphragm, and the stomach with volvulus had herniated into the thorax through the defect. The hernia was considered to be iatrogenic. The diaphragmatic defect was large, and the diaphragm was thinning. We closed the defect by mesh repair. Laparoscopic mesh repair of the diaphragmatic hernia could be performed safely and with minimal invasiveness.